THE STUDENTS’ ABILITY TO IDENTIFY NOMINAL AND VERBAL SENTENCES IN ENGLISH OF GRADE VIII - Hari Indah Utari; Iskandar Zulkarnain; Meida Rabia Sihite (EXCELLENCE: Journal of English and English Education, 2021)
This study was conducted by using descriptive qualitative design. The objective of this study was to find out the students’ ability in identifying nominal and verbal sentences. The subject of the research was of grade VIII at SMP Teladan Sei Rampah academic year 2018-2019. The total number the subject was 20 students. To obtain data, a grammar test was administered to the students. After the data had been analyzed, it was found that the students were able to identify nominal and verbal sentences in English. Thus, it was concluded that the students’ of grade VIII at SMP Teladan Sei Rampah academic year 2018-2019 were able to identify nominal and verbal sentences in English.